2008
DOI: 10.1097/mlr.0b013e31815dc5d2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trauma Exposure and Post-Traumatic Stress Disorder on Healthcare Utilization Among Primary Care Patients

Abstract: Background-Trauma exposure and post-traumatic stress disorder (PTSD) increase healthcare utilization in veterans, but their impact on utilization in other populations is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 20 publications
5
57
0
Order By: Relevance
“…Because of the high rates of trauma and PTSD among patients in primary care (Gillock et al, 2005; Kartha et al, 2008; Liebschutz et al, 2007), and the comorbidity of trauma exposure and PTSD with physical health outcomes (Kroenke et al, 2007; Sareen et al, 2005), a trauma-informed care approach seems warranted. Without provider awareness, trauma exposure may go undetected, and negatively affect patient-provider relationships and patients’ engagement in health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high rates of trauma and PTSD among patients in primary care (Gillock et al, 2005; Kartha et al, 2008; Liebschutz et al, 2007), and the comorbidity of trauma exposure and PTSD with physical health outcomes (Kroenke et al, 2007; Sareen et al, 2005), a trauma-informed care approach seems warranted. Without provider awareness, trauma exposure may go undetected, and negatively affect patient-provider relationships and patients’ engagement in health care.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with trauma/PTSD also report more negative provider interactions and perceptions (Bassuk, Dawson, Perloff, & Weinreb, 2001; Green et al, 2012). Although trauma-exposed patients, and patients diagnosed with PTSD, are common in primary care (Gillock, Zayfert, Hegel, & Ferguson, 2005; Kartha et al, 2008; Liebschutz et al, 2007), primary care providers (PCPs) often feel unprepared when dealing with them (Green et al, 2011; Rodriguez, Bauer, McLoughlin, & Grumbach, 1999; Sugg & Inui, 1992). Programs that address communication with trauma survivors could enhance PCP skills.…”
mentioning
confidence: 99%
“…Several studies have identified a positive association between combat related post-traumatic stress disorder (PTSD) and increased healthcare utilization (19)(20)(21)(22). Kartha et al (23) found that trauma exposure was associated with greater mental healthcare utilization among patients presenting to primary care clinics, and the existence of PTSD explained only part of this association.…”
Section: Methodsmentioning
confidence: 99%
“…One US study identified by the searches reported healthcare utilisation, derived from electronic medical records, for civilian primary care patients, including a proportion who had current PTSD. 136 This study reported an incidence rate ratio of 2.22 (adjusted for age, sex, income, substance dependence, depression and comorbidity) for hospitalisation in subjects with PTSD compared with those without PTSD. Unadjusted mean number of hospitalisations among the PTSD group was 0.43 compared with 0.18 in those without PTSD.…”
Section: Studies Reporting Short Form Questionnaire-36 Items Scoresmentioning
confidence: 99%